Obesity is associated with breast cancer in African American but not Hispanic women in South Los Angeles - Sarkissyan, Marianna (2011)
BACKGROUND: Obesity is considered a risk factor for breast cancer. Modifying life-styles that reduce obesity offers the potential for prevention and improvement of outcomes from cancer. The effects of obesity and breast cancer in African-American women and Hispanic women have been explored in a limited number of studies. The aim of this study is to investigate the association of obesity with breast cancer in our minority cohort. METHODS: This is a cross-sectional study of 471 African-American and Hispanic women with and without breast cancer in South Los Angeles. Information regarding BMI and clinical factors were obtained by medical record abstraction. Logistic regression with multivariate analysis was used for analysis. Kaplan Meier survival analysis was used to assess disease-free survival. RESULTS: Women with breast cancer were more likely to be obese (BMI>30) than women without breast cancer (OR=2.0; P-value=0.01). There was a significant association of being overweight or obese and breast cancer in postmenopausal women (OR=2.3; P-value=0.03 and OR=2.9; P-value<0.01, respectively). We found that an association of obesity with breast cancer was significant only in African-American women (OR=2.70; P-value<0.01), especially postmenopausal African American women (OR=4.8; P-value<0.01). There was a borderline significant association of obesity with later stage of diagnosis (P-value = 0.06). Furthermore, there was an association of higher BMI (in both cut-off points of 30 and 28 kg/m^2) with poorer disease-free survival (P-value = 0.045 and 0.019, respectively). CONCLUSION: Our data suggest an association of obesity with breast cancer, especially in postmenopausal women and most significantly in the African-American cohort.